Teaching the Common Core Math Standards with Hands-On Activities, Grades K-2 - Erin Muschla, Judith A. Muschla, Gary Robert Muschla (Jossey-Bass teacher, 2014)
Start young children off with Common Core math using these innovative activities Teaching the Common Core Math Standards with Hands-On Activities, Grades K-2 provides teachers with the help they need to begin teaching to the new standards right away. The book outlines the Common Core math standards from kindergarten to second grade, providing one classroom-ready activity for each standard, plus suggestions for variations and extensions for students of different learning styles and abilities. Along with teaching the required mathematical concepts and skills, many of the activities encourage collaboration, technology utilization, written and oral communication, and an appreciation of the significance of mathematics in modern life. As the Common Core is adopted across the nation, teachers are scrambling to find information on CCSS-aligned lesson planning and classroom activities. This comprehensive guide answers that need, providing both the background information and practical, applicable guidance that can bring the Common Core into the classroom today. The activities include: * Abstract and critical thinking using mathematical reasoning * Problem-solving strategies and calculation proficiency * Math fluency, and an understanding of mathematical concepts and skills * Applying mathematical understanding to real life problems Early confidence and success in math is critical to a student's future performance. Math anxiety and a shaky foundation can hinder a student's potential far into the future, giving elementary math teachers a huge role in shaping their students' academic lives. The Common Core has set the bar, and Teaching the Common Core Math Standards with Hands-On Activities, Grades K-2 brings the standards to life.